Estimation of stability derivatives for a planar wedge in the newtonian limit - Crasta, Asha; Khan, Sher Afghan (www.iosrjournals.org, 2014)
The present work contains an analytical method derived using Ghosh’s Hypersonic similitude to predict the aerodynamic stability derivatives of a Planar Wedge in the Newtonian limit. It uses the strip theory developed by Ghosh’s where span wise strips are independent of each other, to obtain the expressions for stiffness and damping derivatives in pitch for a planar wedge in the Newtonian limit. The present theory predicts the stability derivatives of a planar wedge for a wide range of geometrical and flow parameters. The knowledge of these stability derivatives is essential to freeze and arrive at the geometrical as well as the kinematic similarity parameters before we go for exhaustive computations and experimental studies. The present method predicts the stability derivatives in pitch for a planar wedge with remarkable computational ease, which is very handy at the design stage. The expressions derived for stability derivatives become exact in the Newtonian limit. It is found that stiffness derivative linearly varies with the pivot position. It is also observed that the centre of pressure moves towards the trailing edge and this shift is quite high at high angles of attack. Hence, this behavior could be utilized to stabilize the aerospace vehicle from the static stability point of view. In the case of damping derivative since the expression for the damping derivative is non-linear and the same has been reflected in the results. However, the behavior remains linear till angle of attack fifteen degrees, later the trend is non-linear.